2014
DOI: 10.1002/aenm.201401228
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Radical and Cationic Cross‐Linking in High‐Efficiency, Low Band Gap Solar Cell Polymers

Abstract: Dithienogermole‐co‐thieno[3,4‐c]pyrroledione (DTG‐TPD) polymers incorporating chemically cross‐linkable sidechains are reported and their properties compared to a parent polymer with simple octyl sidechains. Two cross‐linking groups and mechanisms are investigated, UV‐promoted radical cross‐linking of an alkyl bromide cross‐linker and acid‐promoted cationic cross‐linking of an oxetane cross‐linker. It is found that random copolymers with a 20% incorporation of the cross‐linker demonstrate a higher performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 64 publications
2
28
0
Order By: Relevance
“…This is in agreement with the results of Heeney and co-workers [32] discussed above, who have shown that just 20% of crosslinkable groups result in sufficient device stabilization.…”
Section: Application Of Crosslinking In Organic Photovoltaicssupporting
confidence: 82%
See 2 more Smart Citations
“…This is in agreement with the results of Heeney and co-workers [32] discussed above, who have shown that just 20% of crosslinkable groups result in sufficient device stabilization.…”
Section: Application Of Crosslinking In Organic Photovoltaicssupporting
confidence: 82%
“…Heeney and co-workers [32] compared derivatives of the low bandgap polymer PDTG-TPD with both bromine and oxetane functional groups (Figure 2). The pure polymers can both readily be crosslinked.…”
Section: Application Of Crosslinking In Organic Photovoltaicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bulk heterojunction system exhibits less thermal stability since it likely undergoes macrophase segregation of the blend components with fullerene domain growing with time and thermal annealing . Hence, various strategies have been developed to stabilize the photoactive layer morphology by restricting the molecular diffusion within the blend such as introducing intermolecular cross‐linking , compatibilizer , and side‐chain engineering .…”
Section: Degradation and Stability Issues Of Polymer Solar Cellsmentioning
confidence: 99%
“…Reactive bonding has been explored in polymeric solar cells with side chain functionalization by bromide, oxetane, azide and other groups . Devices with crosslinked polymers demonstrated enhanced thermal stability, resistance to solvents and overall lifetime improvement . Immiscible blends of elastomers and semicrystalline insulators commonly fracture at polymer interfaces, and improved polymer compatibility has been proven to increase cracking resistance .…”
Section: Introductionmentioning
confidence: 99%